Tie-dye textile processing technique with natural pigments applied to organic cotton - Perini , Anerose; Candido , Luis Henrique Alves (Seven Editora, 2023)
The article starts from the discussion about the change in consumer culture and popularity of handmade, which occurred in 2020 during the pandemic. The study focuses on the resurgence of manual techniques and the use of tie-dye textile processing as a fashion trend. The general objective is to describe the tie-dye technique, explored in the context of natural dyeing, and to develop natural pigments for artisanal textile processing. The article is divided into two parts: the first presents a bibliographic research on sustainable processes, dyeing and organic fiber of cotton, while the second part describes an exploratory research on the processes of textile processing using the tie-dye technique with natural plant extracts. DOI:https://doi.org/10.56238/alookdevelopv1-055